Common Fixed Point Theorem for Four Weakly Compatible Self Maps with E.A Property of a Fuzzy G - Metric Space - P. Senthilkumar,; , P. Thiruveni (International Journal of Mathematics And its Applications, 2023)
In this paper we analyse the common fixed point theorem for four weakly compatible self maps with (E.A) property of a G - fuzzy metric space. Some of the inclusions is given to prove the new way of approach for common fixed point theorem.